2019
DOI: 10.2217/fmb-2018-0308
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Vibrio Parahaemolyticus Infections Caused by the Pandemic Clone

Abstract: Vibrio Parahaemolyticus infections caused by the pandemic clone have become a global public health issue. The pandemic clone includes over ten sequence types and 49 serotypes. Several markers such as toxRS/new, orf8 and genomic islands were considered specific for pandemic strains, but subsequent studies later confirmed a lack of specificity. Thus, identifying stable indicators for the pandemic clone is still an open question. In recent years, several environmental pandemic strains are growing, constituting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 94 publications
0
16
0
Order By: Relevance
“…Recently, V. parahaemolyticus has become the leading cause of seafood-borne gastroenteritis (14). A recent phylogenetic analysis of pandemic V. parahaemolyticus isolates (emerged in 1996), and prepandemic isolates (isolated in the 1980s) suggested that the prepandemic strains initially acquired a genomic island containing thermostable direct hemolysin gene (tdh) and a toxRS new region (15); subsequent genomic analysis revealed that acquisition of seven novel genomic islands converted them into pandemic O3:K6 isolates within a decade (16).…”
mentioning
confidence: 99%
“…Recently, V. parahaemolyticus has become the leading cause of seafood-borne gastroenteritis (14). A recent phylogenetic analysis of pandemic V. parahaemolyticus isolates (emerged in 1996), and prepandemic isolates (isolated in the 1980s) suggested that the prepandemic strains initially acquired a genomic island containing thermostable direct hemolysin gene (tdh) and a toxRS new region (15); subsequent genomic analysis revealed that acquisition of seven novel genomic islands converted them into pandemic O3:K6 isolates within a decade (16).…”
mentioning
confidence: 99%
“…Due to the increasing global incidence of foodborne gastroenteritis caused by V. parahaemolyticus (Rezny and Evans, 2020), it is imperative to reevaluate the pathogenicity of this bacteria using modern tools. WGS has played an important role in analyzing the evolution of V. parahaemolyticus and revealing the mechanism of their rapid serotype conversion (Han et al, 2019). However, the uncertainty of pathogenic difference on V. parahaemolyticus remains the difficulty providing complication to its virulence and pathogenic prediction, which reflects in the different isolating sources, geographic positions and infecting concentration correlation.…”
Section: Discussionmentioning
confidence: 99%
“…V. parahaemolyticus is the leading causal agent of human acute gastroenteritis and has become a global public health issue (Letchumanan et al, 2014;Han et al, 2019). V. parahaemolyticus serotyping is considered to be the initial step for timely detection and source tracking of vibriosis outbreaks and can provide historical and comparable data for the surveillance of V. parahaemolyticus infections on a global scale (Han et al, 2016;Baker-Austin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, V. parahaemolyticus is recognized as the leading cause of foodborne disease in China (Liu et al, 2018). Recent studies have found that pandemic V. parahaemolyticus strains are responsible for approximately 50%-80% of all V. parahaemolyticus cases in many countries, including India, Peru, Mexico and Chile (Han et al, 2019). In addition, a newly emerging shrimp disease, acute hepatopancreatic necrosis disease (AHPND), is known to be caused by strains of V. parahaemolyticus that contain a unique virulence plasmid.…”
Section: Introductionmentioning
confidence: 99%